Orchids of Kenya - Stewart, Joyce 1936-2011 (St. Paul's Bibliographies, 1996)
"This, the first book to be devoted to the orchids of Kenya, deals with all the epiphytic species, the lianes in the genus Vanilla, and lastly, the terrestrial kinds. Two thirds of the species are illustrated in colour, several in close-up. A chapter covering the conservation efforts of the National Museum of Kenya is also included."--NHBS Environment Bookstore.
Keywords: Orchids -- Kenya; Orchideen; Kenia